Increased Lipocalin‐2 in the retinal pigment epithelium of Cryba1 cKO mice is associated with a chronic inflammatory response. Issue 6 (25th September 2014) - Valapala, Mallika; Edwards, Malia; Hose, Stacey; Grebe, Rhonda; Bhutto, Imran A.; Cano, Marisol; Berger, Thorsten; Mak, Tak W.; Wawrousek, Eric; Handa, James T.; Lutty, Gerard A.; Samuel Zigler, J.; et al.
Summary Although chronic inflammation is believed to contribute to the pathology of age‐related macular degeneration (AMD), knowledge regarding the events that elicit the change from para‐inflammation to chronic inflammation in the pathogenesis of AMD is lacking. We propose here that lipocalin‐2 (LCN2), a mammalian innate immunity protein that is trafficked to the lysosomes, may contribute to this process. It accumulates significantly with age in retinal pigment epithelial (RPE) cells of Cryba1 conditional knockout (cKO) mice, but not in control mice. We have recently shown that these mice, which lack βA3/A1‐crystallin specifically in RPE, have defective lysosomal clearance. The age‐related increase in LCN2 in the cKO mice is accompanied by increases in chemokine (C‐C motif) ligand 2 (CCL2), reactive gliosis, and immune cell infiltration. LCN2 may contribute to induction of a chronic inflammatory response in this mouse model with AMD‐like pathology.